Dystocia Due to Dicephalus Tetrabrachius Thoracopagus Dipus Dicaudatus Monster in A Murrah Buffalo: A Case Report - Hitesh,; Kumar, S.; Singh, G.; Pradeep,; Dalal, J. (The Indian Journal of Animal Reproduction, 2021)
A Murrah buffalo suffering from dystocia due to a monster was referred to  Veterinary Clinical Complex. On per vaginal examination, two heads and four  forelimbs were present in the birth canal. A lot of manipulation was already had  been done in the field therefore it was decided to go for caesarean section and a  conjoint monster was delivered.
Keywords: Congenital defect; Caesarean section; Dystocia; Monster; Murrah